Protozoarios y helmintos intestinales en adultos asintomáticos del estado Zulia, Venezuela - Rivero de R Zulbey; Calchi L Marinella; Acurero Ellen; Uribe Ismael; Villalobos P Rafael; Fuenmayor B Alexis; Roo Jesús (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2012)
Abstract: Prevalence studies for intestinal parasites are usually performed on children, since they are the most susceptible to these infections; however, this research was conducted to assess the situation in adults. Stool examination was performed on 95 asymptomatic persons over 18 years old, from three different locations in the state of Zulia, Venezuela. Fecal samples were submitted to microscopic examination with SSF-Lugol and the concentration method with formalin ether. Sixty-four individuals (67.36%) had one or more species of intestinal parasites and of these, 81.25% had at least one parasite pathogenic for humans. Thirty-one individuals had more than one parasite species (polyparasitism), with a maximum of three species per host. Seven intestinal protozoa species were identified, including pathogens and commensals, as well as 2 species of helminths. Protozoosis cases predominated (93) over helminths (10). The greatest frequencies corresponded to Blastocystis sp. among protozoa and Ascaris lumbricoides among helminths; also, there was a predominance of A. lumbricoides and Trichuris trichiura in the community Los Pescadores, when comparing the three communities studied. The most frequent parasitic association was Blastocystis sp. with several amoebas. This study found a high prevalence of intestinal protozoa and particularly Blastocystis sp. Resumen: Los estudios de prevalencia de enteroparásitos generalmente se efectúan en población infantil, por ser la más susceptible a estas infecciones; sin embargo, para evaluar la situación en adultos se realizó la presente investigación. Se efectuó el examen coproparasitológico a 95 personas asintomáticas mayores de 18 años, provenientes de 3 diferentes localidades del estado Zulia, Venezuela. Las muestras fecales se sometieron al examen microscópico con SSF-Lugol y método de concentración con formol-éter. 64 individuos (67,36%) presentaron una o varias especies de parásitos intestinales y de éstos, el 81,25% presentaba al menos un parásito patógeno para los humanos. 31 individuos presentaron más de una especie parasitaria (poliparasitismo), con un máximo de 3 especies por hospedador. Se identificaron 7 especies de protozoarios intestinales incluyendo patógenos y comensales, así como 2 especies de helmintos. Predominaron los casos de protozoosis (93) sobre las helmintiasis (10). La mayor frecuencia correspondió a Blastocystis sp. entre los protozoarios y Ascaris lumbricoides entre los helmintos, así mismo, existió un predominio de A. lumbricoides y Trichuris trichiura en la comunidad Los Pescadores, al comparar las tres comunidades estudiadas. La asociación parasitaria más frecuente fue Blastocystis sp. con varias amibas. Este estudio detectó una elevada prevalencia de protozoarios intestinales y particularmente de Blastocystis sp.